Dimensi Edukatif pada Kisah-Kisah Al-Qur'an - Siswayanti, Novita (Lajnah Pentashihan Mushaf Al-Qur'an, 2010)
The stories in Qur'an are AllahÃ¢â‚¬â„¢s decrees which convey more beau-tiful values beyond any religious text ever written. It is the holiest scripture and is writtenÃ‚Â in a wonderful, understandable, and attract-ive language humbly conveying a vast amount of information about life and events that happened in the past. ItÃ¢â‚¬â„¢s aim is to be an object of reflection for human beings living in this age and the future. Even more so, the stories in Al-Qur'an also entail an educative function providing learning materials,Ã‚Â and teaching methods, regarding the transformative power of Islam and the internalization of true religious values.